2015
DOI: 10.1242/dev.122465
|View full text |Cite
|
Sign up to set email alerts
|

Otx2 is a target of N-myc and acts as a suppressor of sensory development in the mammalian cochlea

Abstract: Transcriptional regulatory networks are essential during the formation and differentiation of organs. The transcription factor N-myc is required for proper morphogenesis of the cochlea and to control correct patterning of the organ of Corti. We show here that the Otx2 gene, a mammalian ortholog of the Drosophila orthodenticle homeobox gene, is a crucial target of N-myc during inner ear development. Otx2 expression is lost in N-myc mouse mutants, and N-myc misexpression in the chick inner ear leads to ectopic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…We propose that Otx2 regulates the timing of marginal cell development through a de-repression mechanism, whereby Otx2 expression must be extinguished from marginal cell progenitors in order for their development to proceed. In agreement with this model, a recent study demonstrated that mice lacking Otx2 in the inner ear showed ectopic expression of marginal cell markers along the entire lateral wall of the cochlear duct (Vendrell et al 2015). Moreover, reduction of ectopic Otx2 expression in the marginal cell territory of Esrp1 −/− ;Fgf9 +/− embryos coincided with the recovery of the stria vascularis.…”
Section: Discussionmentioning
confidence: 53%
“…We propose that Otx2 regulates the timing of marginal cell development through a de-repression mechanism, whereby Otx2 expression must be extinguished from marginal cell progenitors in order for their development to proceed. In agreement with this model, a recent study demonstrated that mice lacking Otx2 in the inner ear showed ectopic expression of marginal cell markers along the entire lateral wall of the cochlear duct (Vendrell et al 2015). Moreover, reduction of ectopic Otx2 expression in the marginal cell territory of Esrp1 −/− ;Fgf9 +/− embryos coincided with the recovery of the stria vascularis.…”
Section: Discussionmentioning
confidence: 53%
“…This ventrolateral domain has been shown to express transcription factors such as Otx2 and Ecel1 (Bok et al, 2007; Lin et al, 2005; Riccomagno et al, 2002) that become restricted to Reissner’s membrane. Recent data suggest that one function of Otx2 is to repress prosensory fates in the ventrolateral region of the cochlear duct, as Otx2 conditional mutant mice develop ectopic Sox2 + prosensory regions hair cells in place of Reissner’s membrane (Vendrell et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Kölliker’s organ derives from the antero-ventral region of the otocyst and expresses Lfng and Fgf10, and also overlaps somewhat with Sox2 expression (Morsli et al, 1998; Ohyama et al, 2010; Pauley et al, 2003; Urness et al, 2015). The outer sulcus derives from the postero-ventral region of the otocyst that expresses a stripe of Bmp4 (Morsli et al, 1998; Ohyama et al, 2010; Roberts et al, 2012); and the roof of the cochlear duct, which will ultimately form Reissner’s membrane, derives from the ventro-lateral otocyst that expresses Otx2 (Bok et al, 2007; Koo et al, 2009; Lin et al, 2005; Morsli et al, 1999; Vendrell et al, 2015). As the cochlear duct grows, these four domains elongate in a manner reminiscent of toothpaste with four stripes being squeezed out of a tube.…”
Section: Discussionmentioning
confidence: 99%
“…Morphogens (and transcription factor genes) are depicted by a specific color and downstream genes that are predicted to be direct targets are connected by lines of the same color. If the putative association between a signaling pathway and a downstream affected gene is more likely to be indirect based on available evidence, then the two are connected by an interrupted line (shown as −−//−−) and dark blue dashed connector lines…”
Section: Secreted Signals Regulate Transcription Factors To Specify Dmentioning
confidence: 99%
“…The sensory domain, the organ of Corti, encompasses the medial SC, IHC, lateral SC and OHC. IHC, inner hair cell; OHC, outer hair cell; SC, supporting cell…”
Section: Secreted Signals Regulate Transcription Factors To Specify Dmentioning
confidence: 99%